Multifunctional Lightweight Mortars for Indoor Applications to Improve Comfort and Health of Occupants: Thermal Properties and Photocatalytic Efficiency - Giosuè, Chiara; Pierpaoli, Mattia; Mobili, Alessandra; Ruello, Maria Letizia; Tittarelli, Francesca (Frontiers in Materials, 2020)
A new generation of smart building materials, able to passively improve the indoor environment and the comfort of occupants owing to their interaction with the surrounding environment, can be addressed. This paper investigates the use of three highly porous aggregates to manufacture hydraulic lime-based multifunctional mortars to be used as indoor finishes. The same water/binder ratio was used for each mortar mix, and conventional calcareous sand was totally replaced by volume with zeolite, silica gel and activated carbon. Nanosized titanium dioxide was added to award a photocatalytic behaviour under UV-radiation to the mortars. Results show that, as expected, when highly porous aggregates are used, mortars absorb more water by capillary suction. However, even though the mortars manufactured with lightweight aggregates have a lower density, the mechanical behaviour of zeolite and activated carbon mortars are comparable or even higher than those of sand mortars thanks to an optimum ITZ between the binder paste and the aggregate. The photocatalytic activity, in terms of photocatalytic NOx degradation efficiency and selectivity of unwanted produced NO2, results to be optimal when silica gel-based mortar is tested. Additionally, the thermal insulation properties are enhanced up to 40% by using all the unconventional aggregates.